Goby spotting: An updated guide to coral gobies (Genus: Gobiodon) in the Indo-Pacific Region - Hildebrandt, Courtney A.; Froehlich, Catheline Y. M.; Klanten, O. Selma; Wong, Marian Y. L. (Zootaxa, 2025)
Genus Gobiodon are obligate coral dwelling cryptic fishes. Gobiodon form a mutualistic relationship with host scleractinian corals, making them integral to coral reef ecosystem functioning. Despite this, they are often omitted from fish assemblage studies, biodiversity surveys and coral reef fish guides due to confusion on species identification. The guide aims to provide a comprehensive description of the main diagnostic features for the majority of Gobiodon species distributed throughout the Indo-Pacific region. Species of the genus can be observed occupying host corals of the genera Acropora, Stylophora, Hydnophora and Echinopora on coral reefs in the Pacific and Indian Oceans. Gobiodon species are known for their cryptic behaviours and are distinguishable using body colouration and colour markings. There are 31 described species, 26 of which have undisputed species status and sufficient data to include in this guide. We provide live colouration descriptions, known coral hosts, reef habitats and geographic ranges for each species. Recent developments in understanding the sociality and genetic relationships of this genus have also been incorporated. Useful field resources such as an identification key, occurrence table with accompanying map, and a colour plate of the encompassed species, have been included.